Variabilidade genética em populações de Jabiru mycteria (Lichtenstein, 1819) e Mycteria americana (Linneaus, 1758) (Aves, Ciconiidae): fluxo gênico e filogeografia - Lopes, Iara Freitas (2006)
This study evaluates the levels of variability, genetic structure, and phylogeographical patterns of wild populations of Jabiru Storks (Jabiru mycteria) and Wood Storks (Mycteria americana). These species belong to the family Ciconiidae and present similar morphology, distribution, and ecological requirements. However, the Jabiru Stork is resident and Wood Stork is migratory. Sequences of 549 base pairs (bp) of the first domain of the mitochondrial DNA (mtDNA) control region (CRI) and 822 bp of ND2 gene (ND2), and four heterologous microsatellite loci were used in a survey covering the entire range of Jabiru Storks (72 specimens from Central America, northern and central South America). A lack of diversity was detected in both mtDNA fragments of Central American samples analyzed. The smaller population size of Central American Jabiru Storks population and its demographic decline were potentially responsible for the lower variability observed in this area. Significant genetic differentiation was detected among locations (CRI, Фst = 0.1767; ND2, Фst = 0.4442; microsatellites, Fst = 0.1044). The recent habitat fragmentation and the limited dispersal of Jabiru Storks were likely causes of the high level of differentiation that we detected. Samples of Wood Storks collected in eight Pantanal colonies (n = 48) and eight southeast United States (US) colonies (n = 40) were analyzed using CRI sequences (464bp). A lack of differentiation was detected among colonies in the Pantanal (Fst = -0.015) and also among those sampled in the US (Fst = -0.043), suggesting high levels of gene flow among colonies, or even recent colonization followed by expansion in those areas. A further comparison between Pantanal and US samples revealed significant genetic structure (Fst = 0.059), which indicates that gene flow is limited between these population units. The phylogeographical analysis suggested a historical relationship between Pantanal and US populations. We hypothesize that during the last glaciation maximum, birds moved to more climatically stable areas near the equatorial region, where higher levels of gene flow then occurred. Demographic expansions in the Pantanal region was evidenced in the mtDNA analysis of both species, and might be associated with the recent formation of this wetland areas following increased temperatures and humidity in the Holocene.